Squatters and housing issues in urban development: a Malaysian legal perspective - Mohamad, Nor Asiah; Sufian, Azlinor (2007)
In the process of urban planning there should be a proper system of land management. There are a few primary areas which need to be considered in the urban land management system such as the aspect of development control, land tenure, land acquisition, land administration, land taxation and many others. In this paper a study will be made on the issue of squatters and housing as this is also related to urban land management. Being a developing country undoubtedly Malaysia is facing a crisis of urban squatters which has become a challenge for the local authorities as well as the federal government. This paper will address this issue by examining the Malaysian housing policy towards providing quality and affordable housing for the lower income group in urban areas. Discussion on this topic will relate to the application of various laws and regulations pertaining to local authorities, planning and land law. It is the aim of this paper to present the legal issues relating to squarrets and their appeal for equitable rights and opportunities for housing. This paper also seeks to present the approaches which have been used by the Malaysian government, especially the state of Selangor and the Federal Territory of Kuala Lumpur to achieve the objective of "zero squarrets."